DIGITAL TECHNOLOGIES IN PHILOLOGICAL EDUCATION: TRANSFORMATION OF TEACHING METHODS AND RESEARCH PRACTICES - Melikuziyeva Sevinch,Yuldasheva Mamurakhon (International Journal of Literature and Language Studies, 2026)
The article explores the impact of digital technologies on the development of philological education and research. It examines modern tools of digital philology, including corpus linguistics, electronic resources, and online platforms. The transformation of teaching methods for languages and literature in the context of digitalization is analyzed. Special attention is paid to the integration of innovative technologies into the educational process and their influence on the formation of students’ professional competencies. The advantages and limitations of digital tools are identified. The study concludes that a comprehensive approach to the implementation of technologies in philological education is necessary.